Quando elas estão com ele: o funcionamento do discurso das mulheres.com o presidente38 - Serschön, Márcia Vorpagel (2021)
In this work, from the theoretical perspective of Discourse Analysis proposed by Michel Pêcheux, the discourses present on the Facebook page entitled Mulheres com Bolsonaro#17 were analyzed. This research aimed to understand how the effects of meanings, the Discursive Formations (DFs) are sustained in sayings produced in the social network by women in support of the president38. We also seek to mobilize the understanding that sayings are constituted by a discursive memory. Likewise, we understand that the subject of the discourse is constructed from an already-given, that is, it manifests itself in a materiality that is prior to it, shaped by the conditions of production, by the set of rules of society and by the context ideological socio-historical. Discourse Analysis, by understanding the preconstructed as the ways in which the interdiscourse is present intradiscursively, does not detach these functionings from the relationship between ideology and the unconscious, considering it as constitutive of the process of establishing meaning between interlocutors. That said, it appears that the discourse of the women analyzed is the spokesperson for other stabilized discourses. In this sense, we also reflect on a woman's imaginary that is ideologically affiliated with a sexist saying, but that can be affiliated with a feminist saying, because if the woman through liberal feminism is free to do what she wants, however she wants, she is also free to even be affiliated with the president's ideals38, as he identifies with the speech that elected him; the principles of a traditional family, of a good citizen.